2014
DOI: 10.1007/s40141-013-0039-5
|View full text |Cite
|
Sign up to set email alerts
|

PRP: review of the current evidence for musculoskeletal conditions

Abstract: Injection of platelet-rich plasma (PRP) is an evolving treatment option for various musculoskeletal injuries. There is basic scientific evidence that suggests that the various growth factors present in PRP can help to augment the body's natural healing. There are also clinical studies suggesting efficacy for several conditions, particularly tendinopathy and osteoarthritis. This article reviews the definition and first uses of PRP, the basic scientific rationale for its use, and the basic science and evidence f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 74 publications
0
22
0
2
Order By: Relevance
“…Platelet-rich plasma (PRP) refers to a method to concentrate platelet in plasma to a higher level than in the whole blood (Malanga and Goldin, 2014). PRP contains multiple beneficial factors to augment healing, therefore clinical applications of PRP therapy have soared in the last 10 years, especially in spine, sport, and musculoskeletal medicine (Wu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Platelet-rich plasma (PRP) refers to a method to concentrate platelet in plasma to a higher level than in the whole blood (Malanga and Goldin, 2014). PRP contains multiple beneficial factors to augment healing, therefore clinical applications of PRP therapy have soared in the last 10 years, especially in spine, sport, and musculoskeletal medicine (Wu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In the last few decades, the platelet has been widely studied, and it was demonstrated that it has a great potential to deliver a high concentration of growth factors and chemo/cytokines in a concentrated volume of plasma. As a result, different fields of medicine, aiming to augment the repair of tissues with low healing ability, have been applying platelet‐rich plasma (PRP), a preparation of autologous plasma enriched with a platelet concentration above that normally contained in whole blood . Its use speeds up the vascularisation of grafts, reduces post‐surgery morbidity, improves the regeneration of different tissues, and reduces the formation of a scar as it accelerates the maturity and regeneration of the epithelium of wound .…”
Section: Introductionmentioning
confidence: 99%
“…First, it is not possible to determine the relative contributions of the percutaneous ultrasonic tenotomy versus the PRP in the patient's overall improvement. Previous research has demonstrated that PRP alone can improve pain and function in patients with chronic patellar tendinopathy, as well as promote structural healing after patellar tendon graft harvest for anterior cruciate ligament reconstruction [6]. On the basis of this research and the presence of a large defect after the procedure, the senior author chose to augment the tenotomy with PRP.…”
Section: Discussionmentioning
confidence: 99%
“…In these situations, a variety of treatments have been attempted to promote a healing response in the setting of what is now understood to be a chronic, degenerative, “underhealed” histologic state [1]. Such treatments include tendon fenestration (ie, dry needling), injection of autologous blood, neovessel ablation [5], corticosteroid injection, high‐volume paratenon injections [3,5], and the injection of platelet‐rich plasma (PRP) [6]. When these interventions fail, open or endoscopic surgical debridement represents a definitive treatment option with success rates varying from 45% to 100% [1].…”
Section: Introductionmentioning
confidence: 99%